NAZ Barbershop / Nazri Naseem Abdullah - Abdullah, Nazri Naseem (2020)
This business is focused on ownership where I as the owner and the manager of the operation and consists of four employees, two among whom hold important positions in the organization which is manager of administration and manager of marketing. Then just the other two as barber. Naz Barbershop is not the first business service in Alor Gajah, Melaka was located. The purpose of this business is to help people especially men who have difficulty getting what hairstyle they want. In Malaysia, barbershop usually closed at 3 p.m. or 5 p.m. and open at 12 p.m. But at Naz Barbershop, when they finish their work, people can come and cut their hair, because it will open until 9 p.m. And may extend until 10 p.m. If customers are still waiting to get their hair cut. Naz Barbershop will located at 1649, Jalan Baiduri, Taman Baiduri, 78000 Alor Gajah, Melaka. We chose this location because this is an attractive place and the surrounding area is good for a service like barbershop. Other than this, this is one of the important locations because it's close to the town and the residential area. Our service to our customers is any type of haircut such as pompadour, uppercut, undercut, fade cut and many hairstyles. And we also selling goods like pomade and so on.